The decade ahead theoretical perspectives on motivation and achievement - Karabenick, Stuart A.; Urdan, Timothy C. (Bingley, UK : Emerald, 2010)
The Decade Ahead, takes stock of the current state of knowledge in several areas of motivation research and looks forward to the most likely and promising avenues for research in the coming decade. The chapters, from a mix of both new and veteran researchers, summarize the current state of the research in a particular area of motivation and then offer informed speculation about where the research will go in the coming decade. The volume includes chapters on the intersection of motivation and emotion, the influence of motivation research on educational policy, research on implicit motives, the application of motivation research in classrooms, sociocultural approaches to motivation research, and motivation research with African American students. By providing chapters that both sum-up and look forward, this volume offers a useful roadmap for the future of motivation research in a variety of areas.
Self-efficacy in educational settings: recent research and emerging directions / Robert M. Klassen, Ellen L. Usher -- Expectancy-value theory: retrospective and prospective / Allan Wigfield and Jenna Camria -- Up around the bend: forecasts for achievement goal theory and research in 2020 / Chris S. Hulleman, Corwin Senko -- The development of the five mini-theories of self-determination theory: an historical overview, emerging trends, and future directions / Maarten Vansteenkiste, Christopher P. Niemiec, Bart Soenens -- Self-concept as persons' understanding and evaluation of their own actions and experiences: looking backward and forward from where we are / Jack Martin -- Implicit motives: current topics and future directions / Oliver C. Schultheiss, Andreas G. Rösch, Maika Rawolle, Annette Kordik, Stacie Graham -- Interest in the dynamics of task behavior: processes that link person and task in effective learning / Mary Ainley.
Description based on print version record.
Print version record
Keywords: Motivation in education; Educational psychology; Learning; Educational psychology; Psychology -- Education & Training; Education -- Educational Psychology